ANALISIS KONDISI FISIK ATLET PPLOPD CABANG ATLETIK KOTA SALATIGA TAHUN 2025 - Erni Ulatningsih; Buyung Kusumawardhana; Setiyawan Setiyawan (Journal of Physical Activity and Sports (JPAS), 2025)
This study aimed to analyze the physical condition of athletes participating in the Regional Student Sports Training Program (PPLOPD) for athletics in Salatiga City in 2025. The research employed a descriptive quantitative design involving 50 athletes, consisting of male and female participants, selected using a total sampling technique. Data were collected through physical condition tests covering eight components of physical fitness, including speed, endurance, strength, flexibility, and coordination, as well as medical fitness tests conducted by sports medicine professionals. The physical condition test results were converted into total scores ranging from 0 to 80 points and classified into six categories: Very Good, Good, Fair, Poor, Very Poor, and Extremely Poor based on the standards of the Indonesian Athletics Federation (FAI). The results showed that 46% of athletes were in the Good and Very Good categories, 26% were in the Fair category, and 28% were below the Fair category. Although all athletes were declared medically fit to train, variations in physical condition indicated the need for individualized and systematic training programs. This study highlights the importance of periodic physical condition evaluation as a foundation for designing safe, effective, and performance-oriented training programs for student athletes.